2009
DOI: 10.1016/j.ejvs.2009.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Beta Blockers for Peripheral Arterial Disease

Abstract: Currently, there is no evidence to suggest that beta blockers adversely affect walking distance in people with intermittent claudication. Beta blockers should be used with caution if clinically indicated, especially in patients with critical ischaemia where acute lowering of blood pressure is contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Available evidence and extrapolation from the ALLHAT study suggests that major BP-lowering drug classes including diuretics, CCBs and RAS blockers prevent LEAD events with equal efficacy [1276,1277]. Therapeutic use also includes BBs (not primarily tested in ALLHAT) because these drugs have not been shown to worsen the symptoms of intermittent claudication in two metaanalyses [1278,1279]. In an RCT with the vasodilating beta-1 selective BB nebivolol and the nonvasodilating beta-1 selective BB metoprolol in patients with stable claudication [1280], both treatments were well tolerated, and there were no differences in quality of life, ABI and claudication distance.…”
Section: Management Of Patients With Cognitive Dysfunction and Dementiamentioning
confidence: 99%
“…Available evidence and extrapolation from the ALLHAT study suggests that major BP-lowering drug classes including diuretics, CCBs and RAS blockers prevent LEAD events with equal efficacy [1276,1277]. Therapeutic use also includes BBs (not primarily tested in ALLHAT) because these drugs have not been shown to worsen the symptoms of intermittent claudication in two metaanalyses [1278,1279]. In an RCT with the vasodilating beta-1 selective BB nebivolol and the nonvasodilating beta-1 selective BB metoprolol in patients with stable claudication [1280], both treatments were well tolerated, and there were no differences in quality of life, ABI and claudication distance.…”
Section: Management Of Patients With Cognitive Dysfunction and Dementiamentioning
confidence: 99%
“…In the observational study, treatment of patients after myocardial infarction with beta-adrenolytics significantly reduced the risk of coronary events by 53% [62]. Using drugs from this class did not affect the claudication distance in patients with mild or moderate LEAD [63]. However, caution is recommended when using those drugs in patients with critical ischemia, despite the fact that in the observational studies, even in patients with CLTI the clinical outcomes of treatment were non-inferior among the patients treated with beta-adrenolytics to patients not receiving those drugs [64,65].…”
Section: Pharmacotherapy Of Arterial Hypertension In Patients With Lomentioning
confidence: 93%
“…In general, beta-blockers are relatively contraindicated to avoid worsening of PAD symptoms. However, some reports have revealed that beta-blockers do not aggravate the symptoms in patients with mild to moderate PAD Therefore, beta-blockers are effective in PAD patients with co-existing ischemic heart disease or tachycardia [ 98 , 99 ]. Renal artery stenosis is frequently observed in patients with HTN and PAD.…”
Section: Hypertension In Special Situationsmentioning
confidence: 99%